Sulfur Portland cement and preparation method and application thereof
Through the preparation of sulfosilicate cement, combined with calcination of gypsum and specific component proportions, the problem of cement difficulty in taking into account early and later strength and expansion properties is solved, and efficient and low-cost cement preparation is achieved, which is suitable for construction applications.
Patent Information
- Application Number
- CN202411233941.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-27
AI Technical Summary
It is difficult for existing cement to take into account excellent early and late strength and expansion properties at the same time, and the raw material quality requirements are high, the processing cost is high, and the preparation method is complex.
Using sulfosilicate cement, including sulfosilicate cement clinker and gypsum, the amount of sulfosilicate cement clinker and gypsum is adjusted through specific component ratios and calcining temperature control, combined with X-ray diffraction quantitative analysis, to ensure that Sulfurosilicate cement has excellent early and late strength and expansion properties.
It has achieved excellent early-later strength and expansion performance in building applications, is suitable for different building scenarios, and reduces raw material costs and energy consumption, simplifying the preparation process.
Smart Images

Figure CN119191734A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building cement, and in particular relates to sulpho-silicate cement and a preparation method and application thereof. Background Art
[0002] With the advancement of science and technology, the construction industry needs more high-performance cement-based materials. High-performance cement-based materials have the characteristics of low water-cement ratio, high content of cementitious materials, high content of active mineral admixtures, and low content of coarse aggregate. They are accompanied by large shrinkage during the process of coagulation and hardening and service after hardening, and have a high risk of early cracking. The cracking of cement-based materials is an important factor that aggravates deterioration and even structural failure, reducing the service life of buildings. On the other hand, since corrosive ions enter from the outside of cement-based materials, cracks caused by shrinkage will increase the erosion rate and reduce the service life of the structure. Therefore, it is necessary to develop a cement with less or even no shrinkage to meet the needs of construction projects.
[0003] In recent years, research on the shrinkage control of Portland cement has mostly used magnesium oxide (MgO), calcium oxide (CaO), calcium sulfoaluminate (C4A3$) and other expansive components to be added to cement to compensate for the early shrinkage of Portland cement and reduce the probability of cracking of cement-based materials. However, the existing expansive agents have complex components and are expensive. The effects of expansive agents produced by different companies on the performance of Portland cement vary, which is not conducive to the quality control of concrete.
[0004] The existing patent discloses a low-heat silicate cement and its preparation and application. By controlling the dicalcium silicate content to be greater than 40%, the hydration heat release and drying shrinkage value of the cement and the concrete prepared therewith are effectively reduced, which plays a positive role in improving the cracking of the concrete. However, there is a significant defect of low early strength.
[0005] In view of the low early strength of low heat silicate cement, the existing patent discloses that the early strength of low heat silicate cement can be improved to a certain extent by appropriately reducing the dicalcium silicate content to a minimum of 35%, but the improvement is limited and cannot meet the needs.
[0006] The existing patent discloses a method of using C 20 A method of preparing high early strength and low shrinkage composite silicate cement by using A13M3S3 (Q phase) as an early component and low shrinkage silicate cement clinker with low tricalcium silicate content has a certain improvement in early strength, but it is dependent on the early strength component Q phase. Externally added shrinkage or strength regulating components such as Q phase and active MgO are difficult to obtain directly in nature and need to be processed, which increases energy consumption and cost.
[0007] Existing cement has the problem of not being able to simultaneously achieve excellent early and late strength and expansion performance, and the preparation is complicated and has high requirements on the quality of raw materials. Summary of the invention
[0008] Therefore, one of the technical problems to be solved by the present invention is to overcome the defect of existing cement that it cannot simultaneously take into account excellent early and late strength and expansion performance, thereby providing a sulphur silicate cement and its preparation method and application.
[0009] The second technical problem to be solved by the present invention is that the existing cement has high requirements on the quality of raw materials, the raw materials are not easy to obtain, the processing cost of the raw materials is high, and the preparation method is complicated, so as to provide a sulfo-silicate cement and its preparation method and application.
[0010] To this end, the present invention provides the following technical solutions:
[0011] The first aspect of the present invention protects a sulpho-Silicate cement, wherein the sulpho-Silicate cement comprises sulpho-Silicate cement clinker and gypsum;
[0012] Based on the total mass of the sulpho-Silicate cement clinker, the sulpho-Silicate cement clinker comprises 3-50% of C5S2$, 20-70% of C2S, 20-45% of C4A3$, 1-15% of C4AF, and 0-20% of fC$;
[0013] The mass percentage of gypsum in the sulphur silicate cement satisfies the following calculation formula:
[0014]
[0015] Among them, C G : The content of gypsum in sulfo-Silicate cement; Y: The content of C4A3$ in sulfo-Silicate cement clinker; Sg: The content of SO3 in gypsum; M: Gypsum coefficient, M∈[0-4]; A: The content of fC$ in sulfo-Silicate cement clinker; T: The content of C5S2$ in sulfo-Silicate cement clinker.
[0016] In the present invention, the number of each component in the sulfo-silicate cement clinker is tested by an X-ray diffractometer, and the specific method is to perform quantitative analysis after the X-ray diffraction test. The XRD quantitative analysis uses Topas3 software combined with the Rietveld method, and analyzes the sample with zero point displacement, background coefficient, proportional factor, lattice parameter and preferred orientation as fitting parameters; Sg here corresponds to the SO3 content of gypsum, which will not be zero. The SO3 content of different gypsums is detected according to GB / T 176-2017 "Cement Chemical Analysis Method"; the gypsum coefficient (M) is selected artificially according to actual needs, and the specific selection method is based on the demand for cement expansion performance. The value of M increases with the increase of the required cement expansion rate. When the cement expansion rate is 0.02% after 28 days, the M value is 0.8, and when the cement expansion rate is 0.06% after 28 days, the M value is 3.1.
[0017] According to the present invention, the mass ratio of the sulphoportland cement clinker to gypsum is 60-100:0-40.
[0018] According to the present invention, calcium raw materials, silicon-aluminum raw materials, iron correction materials, sulfur raw materials and activators are mixed and calcined to obtain the sulfur-silicate cement clinker.
[0019] According to the present invention, the mass ratio of the calcium raw material, silicon-aluminum raw material, iron correction material, sulfur raw material and activator is (35-65):(20-45):(0-30):(2-30):(0.01-2).
[0020] According to the present invention, the calcareous raw material comprises at least one of limestone, carbide slag, steel slag, marble, marl and chalk.
[0021] According to the present invention, the siliceous and aluminous raw materials include at least one of fly ash, coal gangue, red mud, bauxite, sandstone, clay, shale and mudstone.
[0022] In the present invention, raw materials such as bauxite, fly ash, and steel slag contain iron oxide components, so there is no need to add iron correction materials separately.
[0023] According to the present invention, the sulfur raw material includes at least one of natural gypsum, phosphogypsum, desulfurized gypsum and anhydrite.
[0024] In the present invention, the main component of the desulfurized gypsum is calcium sulfate dihydrate, which is the same as natural gypsum, with a content of ≥93%, and can be used as a sulfur raw material; natural gypsum is a gypsum ore contained in nature, and its main components are dihydrate gypsum and anhydrite.
[0025] According to the present invention, the iron correction material includes at least one of iron tailings, laterite, pyrite and iron powder.
[0026] According to the present invention, the activator includes at least one of fluorite, magnesia ore, phosphorus slag and tourmaline.
[0027] According to the present invention, the calcination temperature is 1200-1300°C and the calcination time is 0.5-2h. The present invention also includes a step of grinding the mixture obtained after mixing before calcination.
[0028] According to the present invention, the content of SO3 in the gypsum is 35-55% based on the total mass of the gypsum.
[0029] According to the present invention, the gypsum includes at least one of dihydrate gypsum, hemihydrate gypsum, anhydrite, phosphogypsum and desulfurized gypsum.
[0030] The second aspect of the present invention protects a method for preparing the aforementioned sulphoportland cement, wherein the preparation method comprises: S1, preparing sulphoportland cement clinker; S2, mixing and grinding the sulphoportland cement clinker with gypsum to obtain the sulphoportland cement.
[0031] According to the present invention, the sulphur silicate cement is ground to a specific surface area greater than 300 m 2 / kg, optional 300-400m 2 / kg.
[0032] In the present invention, the amounts of sulphur silicate cement clinker and gypsum have been described in the first aspect of the invention and will not be described in detail herein.
[0033] The third aspect of the present invention protects the use of the aforementioned sulphoportland cement or the sulphoportland cement prepared by the aforementioned preparation method in the field of construction.
[0034] The technical solution of the present invention has the following advantages:
[0035] 1. The present invention provides a sulpho-Silicate cement, wherein the sulpho-Silicate cement comprises sulpho-Silicate cement clinker and gypsum; in terms of the mass percentage of the sulpho-Silicate cement clinker, the sulpho-Silicate cement clinker comprises 3-50% of C5S2$, 20-70% of C2S, 20-45% of C4A3$, 1-15% of C4AF, and 0-20% of fC$; the amounts of the gypsum and the sulpho-Silicate cement clinker satisfy the calculation formula: Among them, C G : The content of gypsum in sulpho-Silicate cement; Y: The content of C4A3$ in sulpho-Silicate cement clinker; Sg: The content of SO3 in gypsum; M: Gypsum coefficient, M∈[0-4]; A: The content of fC$ in sulpho-Silicate cement clinker; T: The content of C5S2$ in sulpho-Silicate cement clinker; The specific calculation formula in the present invention can accurately adjust the amount of sulpho-Silicate cement clinker and gypsum, so that the sulpho-Silicate cement has excellent early and late strength and expansion performance, is suitable for different construction scenarios such as casting of structural components, crack repairing, etc., and can maintain long-term integrity after use.
[0036] 2. The present invention has low requirements for reaction raw materials, has abundant sources of raw materials and does not require complicated pretreatment steps, and has a simple preparation method, which can reduce costs and energy consumption, and is conducive to large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 This is a photograph of the sulphur silicate cement prepared in Example 1 after being left for 28 days;
[0039] Figure 2 This is a photograph of the sulphur silicate cement prepared in Example 5 after being left for 28 days;
[0040] Figure 3 This is a photograph of the sulphur silicate cement prepared in Comparative Example 1 after being placed for 28 days. DETAILED DESCRIPTION
[0041] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0042] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0043] There is no restriction on the source of raw materials, and the main method is to reuse waste.
[0044] The specific values of the added raw materials and the final products in the examples are all integers.
[0045] Example 1
[0046] This embodiment provides a method for preparing sulpho-Silicate cement, and the specific steps are as follows:
[0047] According to the mass percentage, 42 parts of limestone, 11 parts of carbide slag, 10 parts of bauxite, 6 parts of sandstone, 5 parts of red mud, 25 parts of phosphogypsum and 1 part of tourmaline are mixed evenly, and calcined at 1250°C for 2 hours to obtain sulfo-silicate cement clinker. The sulfo-silicate cement clinker includes 7% C5S2$, 42% C2S, 39% C4A3$, 5% C4AF, 5% fC$, and the rest are impurities.
[0048] Select desulfurized gypsum (M=3.0, Sg=37.59%) for mixing,
[0049] According to the formula, When the amount of sulphur silicate cement clinker is 80 parts, the amount of desulphurized gypsum is 20 parts, mixed and ground to obtain sulphur silicate cement with a specific surface area of 342m 2 / kg, after 28 days Figure 1 As shown, from Figure 1 It can be seen that it remains intact after 28 days.
[0050] Example 2
[0051] This embodiment provides a method for preparing sulpho-Silicate cement, and the specific steps are as follows:
[0052] According to the mass proportions, 56 parts of limestone, 3 parts of bauxite, 21 parts of fly ash, 1 part of iron tailings, 18 parts of anhydrite and 0.5 parts of fluorite are mixed evenly and calcined at 1250°C for 1.5h to obtain sulfo-silicate cement clinker, which includes 13% C5S2$, 35% C2S, 45% C4A3$, 5% C4AF and 2% fC$.
[0053] Select dihydrate gypsum (M=3.6, Sg=35.58%) for mixing,
[0054] According to the formula, C G = 32%, when the amount of sulpho-Silicate cement clinker is 68 parts, the amount of dihydrate gypsum is 32 parts, mixed and ground to obtain sulpho-Silicate cement with a specific surface area of 356m 2 / kg.
[0055] Example 3
[0056] This embodiment provides a method for preparing sulpho-Silicate cement, and the specific steps are as follows:
[0057] According to the weight percentage, 26 parts of steel slag, 20 parts of marl, 11 parts of shale, 16 parts of coal gangue, 26.2 parts of desulfurized gypsum, 0.3 parts of fluorite, 0.2 parts of borate magnesium ore and 0.3 parts of phosphorus slag are mixed evenly and calcined at 1260°C for 0.67h to obtain sulfo-silicate cement clinker. The obtained sulfo-silicate cement clinker includes 20% C5S2$, 46% C2S, 32% C4A3$, 2% C4AF and no fC$.
[0058] Select phosphogypsum (M=0.9, Sg=43.10%) for mixing,
[0059] According to the formula, C G= 2%, when the amount of sulpho-Silicate cement clinker is 98 parts, the amount of phosphogypsum is 2 parts, mixed and ground to obtain sulpho-Silicate cement with a specific surface area of 351m 2 / kg.
[0060] Example 4
[0061] This embodiment provides a method for preparing sulpho-Silicate cement, and the specific steps are as follows:
[0062] According to the weight percentage, 16 parts of steel slag, 35 parts of marble, 5 parts of clay, 16 parts of fly ash, 28.4 parts of desulfurized gypsum, 0.2 parts of fluorite and 0.4 parts of phosphorus slag are mixed evenly, and calcined at 1250℃ for 1h to obtain sulfo-silicate cement clinker, which includes 21% C5S2$, 34% C2S, 40% C4A3$, 3% C4AF and 2% fC$.
[0063] Select phosphogypsum (M=2.7, Sg=43.10%) for mixing,
[0064] According to the formula, C G =7%, when the amount of sulpho-Silicate cement clinker is 93 parts, the amount of phosphogypsum is 7 parts, mixed and ground to obtain sulpho-Silicate cement with a specific surface area of 349m 2 / kg.
[0065] Example 5
[0066] This embodiment provides a method for preparing sulpho-Silicate cement, and the specific steps are as follows:
[0067] According to the weight percentage, 36 parts of carbide slag, 20 parts of steel slag, 16 parts of sandstone, 9 parts of red mud, 2 parts of laterite, 16.7 parts of phosphogypsum, 0.1 parts of fluorite and 0.2 parts of borate magnesium ore are mixed evenly and calcined at 1240°C for 1 hour to obtain sulfo-silicate cement clinker, which includes 3% C5S2$, 53% C2S, 30% C4A3$, 4% C4AF and 10% fC$.
[0068] Without adding gypsum, M=0,
[0069] 100 parts of sulpho-Silicate cement clinker were ground to obtain sulpho-Silicate cement with a specific surface area of 353 m 2 / kg, from Figure 2 It can be seen that the sulphur silicate cement prepared in Example 5 remains intact after being placed for 28 days.
[0070] Comparative Example 1
[0071] This comparative example provides a method for preparing sulphur silicate cement, and the specific steps are as follows:
[0072] According to the steps of Example 5, sulpho-silicate clinker was prepared. According to the mass fraction, 70 parts of sulpho-silicate cement clinker and 30 parts of anhydrite were mixed and ground to obtain sulpho-silicate cement with a specific surface area of 361 m 2 / kg, from Figure 3 It can be seen that the sulphur silicate cement prepared in Comparative Example 1 had broken and disintegrated after 28 days and could not be tested.
[0073] The strength test of the prepared cement was carried out according to the standard GB / T 17671-2021, and the expansion rate test was carried out according to the standard JC / T 313-2009. The test results are shown in Table 1.
[0074] Table 1
[0075]
[0076] Note: “\” means it cannot be tested.
[0077] The sulphur silicate cement prepared by the invention has excellent early and late strength and expansion performance, and can maintain long-term integrity after use.
[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A sulphur-portland cement, characterized in that: The sulpho-silicate cement comprises sulpho-silicate cement clinker and gypsum; Based on the total mass of the sulpho-Silicate cement clinker, the sulpho-Silicate cement clinker comprises 3-50% of C5S2$, 20-70% of C2S, 20-45% of C4A3$, 1-15% of C4AF, and 0-20% of fC$; The mass percentage of gypsum in the sulphur silicate cement satisfies the following calculation formula: Among them, C G : The content of gypsum in sulfo-Silicate cement; Y: The content of C4A3$ in sulfo-Silicate cement clinker; Sg: The content of SO3 in gypsum; M: Gypsum coefficient, M∈[0-4]; A: The content of fC$ in sulfo-Silicate cement clinker; T: The content of C5S2$ in sulfo-Silicate cement clinker.
2. The sulpho-Portland cement according to claim 1, characterized in that The mass ratio of the sulpho-Portland cement clinker to gypsum is 60-100:0-40.
3. The sulphur silicate cement according to claim 1, characterized in that The calcium raw material, the silicon-aluminum raw material, the iron correction material, the sulfur raw material and the activator are mixed and calcined to obtain the sulfur-silicate cement clinker; Optionally, the mass ratio of the calcium raw material, silicon-aluminum raw material, iron correction material, sulfur raw material and activator is (35-65):(20-45):(0-30):(2-30):(0.01-2).
4. The sulphur-portland cement according to claim 3, characterized in that The calcium raw material includes at least one of limestone, carbide slag, steel slag, marble, marl and chalk; And / or, the silicon-alumina raw material includes at least one of fly ash, coal gangue, red mud, bauxite, sandstone, clay, shale, and mudstone; And / or, the sulfur raw material includes at least one of natural gypsum, phosphogypsum, desulfurized gypsum and anhydrite; And / or, the iron correction material includes at least one of iron tailings, laterite, pyrite, and iron powder; And / or, the activator includes at least one of fluorite, magnesia ore, phosphorus slag and tourmaline.
5. The sulpho-Portland cement according to claim 3, characterized in that: The calcination temperature is 1200-1300° C., and the calcination time is 0.5-2 h.
6. The sulpho-Portland cement according to claim 1, characterized in that: The content of SO3 in the gypsum is 35-55% based on the total mass of the gypsum.
7. The sulpho-Portland cement according to claim 1, characterized in that The gypsum includes at least one of dihydrate gypsum, hemihydrate gypsum, anhydrite, phosphogypsum and desulfurized gypsum.
8. A method for preparing sulpho-Portland cement according to any one of claims 1 to 8, characterized in that: The preparation method comprises: S1, preparing sulphur-portland cement clinker; S2, mixing and grinding the sulpho-Silicate cement clinker with gypsum to obtain the sulpho-Silicate cement.
9. The preparation method according to claim 8, characterized in that: The sulphur silicate cement is ground to a specific surface area greater than 300 m 2 / kg, optional 300-400m 2 / kg.
10. Use of the sulpho-Silicate cement according to any one of claims 1 to 7 or the sulpho-Silicate cement prepared by the preparation method according to claim 8 or 9 in the field of construction.
